Will the inclusion of AI anchors enhance the operational performance of live streaming e-commerce supply chains? - Xinyan Yan; Qihui Lu; Di Xiao (PLoS ONE, 2025)
With the rapid growth of the live streaming e-commerce market, traditional live streaming models are encountering mounting challenges, whereas the advent of artificial intelligence (AI) technology has breathed new life into live streaming. This paper delves into the role of the AI anchor and model selection in scenarios both with and without the involvement of the Key Opinion Leader (KOL). Specifically, the AI anchor, whether invested in by the brand or the live streaming platform, is integrated into the regular anchor model (Model NN) and the hybrid model combining the KOL and the regular anchor (Model NK). A series of Stackelberg game models are formulated to compare the sales effort level, AI intelligence level, anchor influence, and the proportion of live streaming time on live streaming e-commerce. The findings suggest that the AI anchor can effectively substitute for the human anchor under certain conditions, particularly when the brand controls the AI intelligence level. To further explore the impact of the AI anchor on decision-making and profits among supply chain participants, the paper offers a thorough analysis of decisions and profits in scenarios both with and without KOL involvement. The results disclose that, under suitable conditions, the incorporation of the AI anchor can substantially enhance the operational efficiency of live streaming e-commerce supply chains, leading to increased profitability for the brand. Notably, the allocation of live streaming time between different anchors in hybrid models significantly influences the profitability of supply chain members. This discovery provides crucial insights for brands in devising live streaming strategies.